1980
DOI: 10.1029/gl007i007p00537
|View full text |Cite
|
Sign up to set email alerts
|

Coincident radar and rocket observations of equatorial spread‐F

Abstract: Coordinated measurements of equatorial spread‐F conducted during July 1979 at the Kwajalein Atoll have yielded the first definitive space‐ and time coincident radar and rocket observations of small scale irregularities and large scale plasma depletions. The results have shown that: (a) During conditions of well‐developed equatorial spread‐F the most intense "in situ" irregularities occurred on the bottomside F‐layer gradient. (b) Within a large scale topside F‐layer depletion radar backscatter and "in situ" ir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

1982
1982
2017
2017

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 69 publications
(23 citation statements)
references
References 17 publications
3
20
0
Order By: Relevance
“…The general collocation of plumes and bubbles, shown by results presented here and elsewhere Tsunoda, 1980a, b;Towle, 1980;Szuszczewicz et al, 1980], implies that backscatterproducing irregularities are primarily generated in regions of low plasma density. This preference for low plasma densities is consistent with the production of these irregularities by the lower-hybrid-drift (LHD) instability [Huba et al, 1978;S §Terlinjnd Goldman, 1980;Huba and Ossakow, 1981].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The general collocation of plumes and bubbles, shown by results presented here and elsewhere Tsunoda, 1980a, b;Towle, 1980;Szuszczewicz et al, 1980], implies that backscatterproducing irregularities are primarily generated in regions of low plasma density. This preference for low plasma densities is consistent with the production of these irregularities by the lower-hybrid-drift (LHD) instability [Huba et al, 1978;S §Terlinjnd Goldman, 1980;Huba and Ossakow, 1981].…”
Section: Discussionmentioning
confidence: 99%
“…Bottomside backscatter, which occurs on both sides of the plume pair, tilt; upward in the direction of the plumes. Because bottomside backscatter occurs along the bottomside -radient of the F layer [e.g., Szuszczewicz et al, 1980;Tsunoda, 1930b], the shape of the bottomside backscatter implies that the plume pair is associated with a large-scale upwelling that has an east-west dimension of approximately 400 km, or more. An association of plumes and upwellings has heen suggested by Tsunoda [19811 and verified by Tsunoda and White [1981].…”
Section: A It Auiiui T 1978 (1041 To 1043 Ut)mentioning
confidence: 99%
See 2 more Smart Citations
“…Woodman and LaHoz (1976) ®rst identi®ed valley region irregularities below the main plumes in the RTI radar maps obtained from Jicamarca. Vickrey et al (1984) studied electron density irregularities observed in the F region valley, which were obtained from ®xed bias LP¯own on two rockets launched from Natal, Brazil (Kelley et al, 1976(Kelley et al, , 1979Costa and Kelley, 1978) and from Kwajalein Atoll (Szuszczewicz et al, 1980Rino et al, 1981;Kelley et al, 1982b). During these twō ights quasi-sinusoidal¯uctuations in the F region valley (170 to 200 km) were observed where the local zero order vertical plasma density gradient nearly vanishes.…”
Section: Intermediate Scale Irregularitiesmentioning
confidence: 99%